The influence of Chinese college teachers' competence for purpose support on students' purpose development. Issue 5 (19th October 2016) - Jiang, Fei; Lin, Shan; Menon Mariano, Jenni
Abstract: Research studies agree on the role formal education can play in facilitating students building a sense of life purpose. This paper examined the influence of Chinese college students' perceived competence of their teachers for supporting purpose on these same college students' purpose status. Portions of the Revised Youth Purpose Survey were adapted for Chinese college student and teacher populations, and then administered to 52 teachers and 213 students from a mid-size teacher training university in north-east China. There was inconsistency between teachers' self-evaluations and students' evaluations, with teachers rating themselves as more supportive of purpose than they were rated by their students. Upperclassmen reported higher levels of teacher competence for supporting purpose than lowerclassmen, and arts teachers were rated as more supportive of purpose than teachers of other subjects . Students who ranked obviously other-oriented goals as their most important purposes also rated their teachers as more competent in purpose support than students who endorsed other types of goals. Significant positive associations were found among students' ratings of teachers for purpose support and reports of purpose from students, including associations with students' purpose search and purpose identification; however, no relationship was found between students' purpose engagement and perceptions of teachers' purpose support.